Effects of Tigernuts on Blood Urea, Uric Acid and Creatinine Levels in the Normal Weight Male Humans - Igbinovia Edokpolor N; Ohiwerei Wisdom O; Festus Oloruntoba O; Ohiwerei Faith O; Onokevbagbe Elisha O (MultiTech Publisher, 2024)
Natural antioxidants are gaining significant attention from nutritionists, food manufacturers, medical professionals, and consumers due to their numerous health benefits. This study explored the potential effects of tigernuts on blood urea, uric acid, and creatinine levels in normal-weight male subjects under resting conditions, as well as the possible mechanisms involved. Methods: A total of forty (40) non-habitual tigernut chewers, aged 18–28 years, participated in the study. After recording the anthropometric data of the control group, the subjects rested for 1 hour and 30 minutes. Urea levels were measured colorimetrically using the Urease-Berthelot’s Method, where urea in plasma was hydrolyzed to ammonia in the presence of urease, and the resulting ammonia was detected photometrically through Berthelot’s reaction. Uric acid was determined using an enzymatic colorimetric method, while creatinine was assessed using the Modified Jaffe’s Method, in which creatinine in the sample reacted with picrate in an alkaline medium to form a colored complex, measured within a short period to minimize interference.On a separate day, 5g of tigernuts were given to the same subjects—who had previously served as controls—to be chewed as a bolus. Findings indicated that tigernuts significantly reduced (P < 0.05) blood urea levels post-consumption (from 16.32 ± 0.759 to 11.76 ± 1.325 mg/dl). However, uric acid levels significantly increased (P < 0.05) following ingestion (from 2.438 ± 0.439 to 4.851 ± 0.393 mg/dl). Blood creatinine levels decreased from 1.778 ± 0.093 to 1.617 ± 0.089 g/dl, though this reduction was not statistically significant. This study suggests that tigernuts have beneficial effects on renal urea and creatinine levels, supporting their consumption for maintaining kidney health